2010
DOI: 10.1186/1471-227x-10-9
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of pulse oximetry in emergency department patients with severe sepsis and septic shock: a retrospective cohort study

Abstract: BackgroundPulse oximetry is routinely used to continuously and noninvasively monitor arterial oxygen saturation (SaO2) in critically ill patients. Although pulse oximeter oxygen saturation (SpO2) has been studied in several patient populations, including the critically ill, its accuracy has never been studied in emergency department (ED) patients with severe sepsis and septic shock. Sepsis results in characteristic microcirculatory derangements that could theoretically affect pulse oximeter accuracy. The purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 26 publications
6
86
0
3
Order By: Relevance
“…With regard to S aO2 predictions, many studies in the literature have been focused on determining the expected differences between the actual S aO2 and the S pO2 values for ICU patients. The average differences between experimentally measured S aO2 values and S pO2 measurements are reported as 2.4-2.75 % with an SD of about 3 % [31][32][33]. The results of this study are in general agreement with these findings.…”
Section: Resultssupporting
confidence: 93%
“…With regard to S aO2 predictions, many studies in the literature have been focused on determining the expected differences between the actual S aO2 and the S pO2 values for ICU patients. The average differences between experimentally measured S aO2 values and S pO2 measurements are reported as 2.4-2.75 % with an SD of about 3 % [31][32][33]. The results of this study are in general agreement with these findings.…”
Section: Resultssupporting
confidence: 93%
“…The bias and 95% CI for limits of agreement in our whole population (2.5% and (Ϫ10.1,15.1)%) were also larger than those reported by most studies in non-hyperleukocytic subjects [24][25][26] but were probably negatively affected by samples with extreme WBC count. Indeed, the bias and 95% CI for limits of agreement that we observed in subjects with WBC count Ͻ 100 ϫ 10 9 /L (0.4% and (Ϫ7.9,8.6)%) are similar to those reported in studies in critically ill 27 and COPD 26 populations. Conversely, the bias and 95% CI for limits of agreement were 3.8% and (Ϫ10.3,18.0)% for WBC count Ͼ 100 ϫ 10 9 /L, whereas one of the largest studies on 102 general ICU subjects reported a bias of only 0.02% with 95% CI for limits of agreement of (Ϫ4.2,4.2)%.…”
Section: Discussionsupporting
confidence: 72%
“…The discrepancy between healthy volunteers examined during the empirical calibration process and patients is further accentuated in neonates 22. The deviation of SpO 2 from SaO 2 is even greater at saturations below 70%–80%,11,23–26 because ethical restrictions prevent manufacturers from reducing SaO 2 below 80% during the calibration process. The inaccuracy associated with the co-oximetry itself (upon which the calibration process is based) is an additional contributing factor to the error in SpO 2 measurement 17…”
Section: The Accuracy Of Pulse Oximetrymentioning
confidence: 99%